2004
DOI: 10.1159/000070813
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Imaging of the Kidney Using Multiparameter Multiphoton Microscopy

Abstract: Intravital optical microscopy provides a powerful means of studying the cell biology in the most physiologically relevant setting. The ability of multiphoton microscopy to collect optical sections deep into biological tissues has opened up the field of intravital microscopy to high-resolution studies of multiple organs. Presented here are examples of how two-photon microscopy can be applied to intravital studies of kidney physiology and the study of disease processes. These include studies of cell vitality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 11 publications
4
53
0
Order By: Relevance
“…Results presented extend previous studies of cultured cells, demonstrating that rifampin inhibits uptake of organic anions by hepatocytes in vivo and provide support for an iterative model of hepatic transport. Although used here to evaluate the effects of chronic rifampin treatment, the ability to analyze processes occurring in the timescale of seconds to minutes also provides intravital microscopy with the unique ability to detect acute, or transient drug effects which, when combined with additional readouts of injury, 43,60,[62][63][64][65][66] provides the potential to characterize the chronology of cholestatic liver injury. Since is both properly sedated and physiologically supported.…”
Section: Discussionmentioning
confidence: 99%
“…Results presented extend previous studies of cultured cells, demonstrating that rifampin inhibits uptake of organic anions by hepatocytes in vivo and provide support for an iterative model of hepatic transport. Although used here to evaluate the effects of chronic rifampin treatment, the ability to analyze processes occurring in the timescale of seconds to minutes also provides intravital microscopy with the unique ability to detect acute, or transient drug effects which, when combined with additional readouts of injury, 43,60,[62][63][64][65][66] provides the potential to characterize the chronology of cholestatic liver injury. Since is both properly sedated and physiologically supported.…”
Section: Discussionmentioning
confidence: 99%
“…Multiphoton excitation imaging was employed to quantitatively reveal microvascular function (Dunn et al, 2003;Molitoris & Sandoval, 2005) as well as glomerular filtration and permeability within kidney with living animals (Kang et al, 2006;Sipos et al, 2007). In a further study, they showed how this nonlinear optical imaging can be used to observe and quantify drug delivery in an intact, living and functioning kidney.…”
Section: In Vivo Drug Screening and Administration In Skin And Kidneymentioning
confidence: 99%
“…While the surface of the kidney is easily imaged by conventional optical microscopy, imaging into the kidney is best approached by MPM. [2,3] However, we have found that MPM is capable of collecting images from only the first two hundred microns into the kidney. Here we evaluate the role of spherical aberration in signal attenuation with depth into fixed and living kidney tissues, and evaluate a simple solution to improve deep-tissue MPM.…”
Section: Spherical Aberration In Deep-tissue Multiphoton Microscopy Omentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Additionally, because multiphoton microscopy is a fluorescence technique, it has the ability to localize multiple specific molecules simultaneously. Multiphoton microscopy has also been shown to allow extended observation of even highly sensitive processes without detectable damage.…”
Section: Introduction -The Role Of Intravital Microscopy In Biomedicamentioning
confidence: 99%